Antibacterial Activity of Scopoletin from Stem Bark of Aleurites moluccana Against Salmonella typhi - Wisnu Cahyo Prabowo; Risna Agustina (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
Background: Based on a previous survey of ethnopharmaceutical studies (local culture), it was known that the use of decoction of candlenut stem bark (Aleurites Moluccana) was used as typhoid medicine in the treatment tradition of the people of East Kalimantan. In antibacterial screening by diffusion test, methanol extract of stem bark A.moluccana showed excellent growth inhibition of Salmonella thypimurium. Working method: Simplicia of A.moluccana stem bark was extracted by maceration using methanol. Maserate was extracted liquid-liquid using n-hexane and ethyl acetate solvents. The hexane and ethyl acetate fraction was monitored for active spots with TLC bioautography. The active compound is separated using vacuum liquid chromatography and radial chromatography. Results: The fraction J of KCV and J2 subfraction results from radial chromatography provides antibacterial activity of S. thpimurium. From the J2 subfraction obtained pure isolates in the form of yellowish needle crystals. The isolate was tested for antibacterial S.thypimurium using the microdilution method with a value of MIC is 250 µg/ml. Based on spectroscopic data and comparing the published spectra of the compound, the elucidation of the isolate is Scopoletin (7-hydroxy-6-methoxycoumarin).